2019
DOI: 10.23736/s0026-4946.19.05367-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sexually explicit internet material and its effects on minors' health: latest evidence from the literature

Abstract: BACKGROUND. Nowadays adolescents and children are more and more exposed to sexually explicit internet material (SEIM), but most parents and healthcare professionals neglect this issue.The aim of the present study is to evaluate the impact of online pornography on minors' health with a specific focus on the effects produced on their behavioural, psychophysical and social development. METHODS. A literature search was performed on PubMed and ScienceDirect in March 2018 with the query "(pornography OR sexually exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…This issue is not unique to Uganda. Principi et al (2019) note that global consumption of pornography in minors can no longer be neglected. Governmental and nongovernmental organizations must work together to develop content that provides youth the opportunity to critically think about pornography and its impact on their sexual health (Principi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This issue is not unique to Uganda. Principi et al (2019) note that global consumption of pornography in minors can no longer be neglected. Governmental and nongovernmental organizations must work together to develop content that provides youth the opportunity to critically think about pornography and its impact on their sexual health (Principi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found that youth from well-to-do households have more disposable income and thus are more likely to misuse drugs leading to high forms of sexual risk-taking behaviours 19 , 20 . Further, these youth are more likely to have access to erotic material through social media which has been linked to the prevalence of a hook-up culture in this population 21 , 22 . For instance, Carmack & Rodriguez (2020) found that higher Facebook usage among female study participants (17- 23 years) was associated with having concurrent sexual partners and the pursuit of hookups 21 .…”
Section: Discussionmentioning
confidence: 99%